Consumers' Meaning-Making of the Starbucks Boycott Campaign in the Context of the Israel-Palestine Conflict - Muhammad Wisnusyah; Delvin Pramata; Melisa Suciati; Bagus Budiono (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2025)
The escalating Israel-Palestine conflict has triggered a wave of global consumer activism, one of which is a boycott campaign targeting multinational brands such as Starbucks. This phenomenon highlights the strong connection between political identity, moral expression, and consumer behavior. This study aims to explore how individuals receive, interpret, and respond to boycott messages against Starbucks within the context of the conflict. Employing a qualitative descriptive phenomenological approach, data were collected through in-depth interviews and digital archive analysis. Informants were purposively selected based on shared characteristics and the intensity of their engagement with the issue. The findings reveal diverse decoding positions, dominant, negotiated, and oppositional, shaped by cultural background, political orientation, personal experience, and brand loyalty. Social media shapes emotional narratives, reinforces symbolic resistance, and shifts perception and consumption behavior. These findings underscore the complexity of political consumerism and demonstrate the active role of consumers in redefining brand image amid socio-political crises. This study offers theoretical and practical contributions to understanding meaning-making dynamics in digital communication and emphasizes the urgency of audience-based approaches in brand communication strategies